Role of Open Surgical Release of A1 Pulley (Annular) in Treatment of Trigger Finger of Hand (Medical Forum Monthly, 2020)
Objective: To study the effectiveness of surgical incision of A1 pulley in treatment of trigger finger.Study Design: Observational study.Place and Duration of Study: This study was conducted at the Department of Orthopedics Islam Medical College of Sialkot during March 2018 to Feb 2019.Materials and Methods: All patients with Trigger Finger are included in our study which include 50 cases. Our study included patients with trigger finger grade III and above as per Qunitell classification. We noted the profile details including Mean age and Gender and recorded treatment results for statistical analysis using SPSS Version-20.Results: In our data trigger finger was found in all 50 subjects with 14 males (28% of total patients) and 36 females (72% of total patients). Mostly patients around 26% felt ring finger and thumb trigger digits, 20% felt middle and index finger digits while only 8% felt it in more than one finger. Amongst the males pain was felt in ring finger joint mostly on right side i.e. 36% while females most affected joint was thumb with 63% left side dominance .The Mean success rate recorded was 77%.Conclusion: Thus the open surgical release of A1 pulley is an effective method for trigger finger management.